The spontaneous generation of magnetic fields at high temperature in SU(2)-gluodynamics on a lattice - Demchik, V.I.; Skalozub, V.V. (Вопросы атомной науки и техники, 2007)
In a lattice formulation of the SU(2)-gluodynamics, the spontaneous generation of the chromomagnetic field at high temperature is investigated. The procedure to study this phenomenon is developed and Monte Carlo simulations are carried out on the lattices 2x8³, 4x8³ and 2x16³ at various temperatures. The χ²-analysis of the obtained data set indicates the presence of the spontaneously created magnetic field in the deconfinement phase. A comparison with the results of other approaches is done.